2017
DOI: 10.1136/bmjresp-2017-000193
|View full text |Cite
|
Sign up to set email alerts
|

Listening panel agreement and characteristics of lung sounds digitally recorded from children aged 1–59 months enrolled in the Pneumonia Etiology Research for Child Health (PERCH) case–control study

Abstract: IntroductionPaediatric lung sound recordings can be systematically assessed, but methodological feasibility and validity is unknown, especially from developing countries. We examined the performance of acoustically interpreting recorded paediatric lung sounds and compared sound characteristics between cases and controls.MethodsPneumonia Etiology Research for Child Health staff in six African and Asian sites recorded lung sounds with a digital stethoscope in cases and controls. Cases aged 1–59 months had WHO se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 33 publications
0
42
0
Order By: Relevance
“…WHO guidelines for frontline health-care providers and community health workers do not include lung auscultation in the diagnostic criteria for child pneumonia. 31,63 Although digital stethoscopes and automated lung sound analysis are emerging areas with the potential to overcome these educational and interpretation limitations, 64,65 additional research is needed before field implementation is feasible.…”
Section: Lung Auscultationmentioning
confidence: 99%
“…WHO guidelines for frontline health-care providers and community health workers do not include lung auscultation in the diagnostic criteria for child pneumonia. 31,63 Although digital stethoscopes and automated lung sound analysis are emerging areas with the potential to overcome these educational and interpretation limitations, 64,65 additional research is needed before field implementation is feasible.…”
Section: Lung Auscultationmentioning
confidence: 99%
“…17,18 2.2 | Digital auscultation sampling in PERCH Sampling of children for lung sound recordings varied by site. 14…”
Section: Perch Enrollmentmentioning
confidence: 99%
“…All study staff were trained to record lung sounds according to a protocol using a commercial digital stethoscope (ThinkLabs ds32a). 14 (Figure 1). The overall recording duration was approximately 1-2 min.…”
Section: Lung Sound Recordingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sensitivity for detection of pneumonia through crepitation detection was only 56% in comparison with plain chest x‐ray, the research displays a novel use for the technology as a bedside assessment tool . This was followed by a large multi‐country case–control study across Africa and Asia where the same technology was used again to identify abnormal pulmonary sounds in paediatric cases of pneumonia . The study concluded that use of this technology in low‐resource settings is feasible and interpretations from the sound recordings can reliably be achieved.…”
Section: Digital Stethoscope Use In Paediatricsmentioning
confidence: 99%